HSK TEST ANXIETY OF CHINESE LANGUAGE LEARNERS IN UNIVERSITY STUDENTS - Junaeny, Arini (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2024)
Anxiety can affect the foreign language learning process negatively. Chinese language as one of the developed foreign languages in Indonesia faces this problem too. In the Chinese language, there is language testing called HSK or Hanyu Shuping Kaoshi. Test Anxiety is one of the students’ problems. Test anxiety in the Chinese language influence in student's learning process and achievement. This research aims to find and analyze students’ Chinese language test anxiety of HSK. The research method is descriptive quantitative and the procedure will be using a questionnaire that gives to the students—the anxiety measurement using Sarason TAS (Test Anxiety Scale). The result is anxiety level belongs to TAS moderate level with data mean 20, 43 points.